2003
DOI: 10.1161/01.cir.0000060542.79482.81
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Determination of Coronary Blood Flow Velocity With Cardiovascular Magnetic Resonance in Patients After Stent Deployment

Abstract: Background-In patients with coronary artery stents, no direct noninvasive coronary artery imaging is possible with magnetic resonance (MR). A well-established method for the assessment of the functional significance of a coronary lesion is the measurement of coronary flow reserve by invasive intracoronary Doppler. The purpose of the study was to determine coronary flow velocity reserve (CFVR) with MR after stent deployment. Methods and Results-Thirty-eight patients after successful PTCA and stent deployment we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 32 publications
1
46
0
1
Order By: Relevance
“…This study, combined with those of prior investigators (13)(14)(15), demonstrates the feasibility of using phase-contrast MR to quantify flow within stented vessels. If these measurements can be preformed in the presence of ISR, this technique may be applied as a noninvasive means of screening for interventional ISR procedures.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…This study, combined with those of prior investigators (13)(14)(15), demonstrates the feasibility of using phase-contrast MR to quantify flow within stented vessels. If these measurements can be preformed in the presence of ISR, this technique may be applied as a noninvasive means of screening for interventional ISR procedures.…”
Section: Discussionsupporting
confidence: 53%
“…Implants with improved MR compatibility have the potential to overcome these limitations (12)(13)(14)(15)(16)(17). The findings of the current study are relevant to clinical conditions, since peripheral arteries and bypass graft vessels are relatively straight and of larger diameter (4 -10 mm).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, measurements performed in close proximity to the stent can reduce the accuracy of the measurements. Nagel et al (9) have shown that measurements at least 1 cm distal to the stent are not influenced by stainless-steel coronary arterial stents. In our study, we measured proximal aortic flow 2 cm distal to the coarctation in order to have a site below the stent placement and to avoid any flow jet from the coarctation.…”
Section: Discussionmentioning
confidence: 99%
“…The flow velocity reserve was 2.26 Ϯ 0.49 at one month and 1.52 Ϯ 0.09 (P Ͻ 0.05) at six months after stent implantation in subjects with restenosis. In a recent study by Nagel et al (83), coronary flow velocity reserve in the artery distal to the stent was measured with MR in 38 patients after successful stent placements. Using a threshold of 1.2 for MR flow velocity reserve, a sensitivity of 83% and a specificity of 94% were achieved for detecting Ն75% stenoses on coronary angiography.…”
Section: Mr Flow Measurement In Coronary Circulationmentioning
confidence: 99%